Analisis Kesuksesan Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) Modul Aset Tetap - Wahyu Budi Utama; Eko Suwardi (Politeknik Ganesha Medan, 2026)
The Institution Level Financial System Application (SAKTI) is a nationally mandated integrated financial system developed to strengthen transparency and accountability in Indonesia’s public financial management. This study aims to evaluate the success of implementing the Fixed Assets Module of SAKTI in working units under Directorate General of Taxes Regional Office – Central Java II, using the DeLone and McLean Information System Success Model. A qualitative case study approach was employed, involving nine informants selected through purposive sampling. Data were collected via literature review, observation, and semi-structured interviews, and analyzed through data reduction, presentation, and conclusion drawing. The results reveal that system quality, information quality, and service quality remain constrained by issues such as data synchronization, limited training, and technical terminology comprehension. In contrast, user satisfaction and net benefits show positive outcomes, especially regarding efficiency, accessibility, and reporting accuracy. Overall, the implementation of the Fixed Assets Module is deemed moderately successful. This study contributes to the literature by providing an in-depth qualitative evaluation of a mandatory public financial system in Indonesia, highlighting the importance of technical support enhancement, regular user training, and improved system integration to optimize the module’s performance and sustainability.